A categoria verbal sob uma perspectiva enunciativa - Batista, Sandra Mariani (2009)
According to history the didactic book has been an object of study in many studies and researches, in which many different theoretical and methodological focuses have been used. Besides the passion that this theme awakes, the didactic book constitutes in fact, an indispensable instructional material for the teacher in the elementary and secondary school, which is used to give a direction to the pedagogical practice in these levels of instruction. Nowadays, the society between the book and the teacher is crossing a moment of meeting and avoiding each other, since both are passing through a period of transition, searching for an identity which reveals the theoretical and political transformation occurred in the educational prospect. Taking this into consideration, the main objective of this work is to analyze how books of a 5th grade of elementary school from different decades present the verb study and if these materials bring an enunciate perspective. As a theoretical reference, Saussure s language conceptions are delineated, the language in Benveniste, as well as his considerations in relation to the analyzing levels, the formal system of enunciation and the categories related to people, space and time, and the light of the Teoria da Enunciação of Émile Benveniste. Considering the grammar and the historical book studies the concept of verb is presented in the following review: Moderna Gramática Portuguesa , by Evanildo Bechara, Gramática Normativa da Língua Portuguesa , by Carlos Henrique Rocha Lima, Gramática de usos do Português , by Maria Helena de Moura Neves, the book Português: Linguagens 5ª série by William Roberto Cereja and Thereza Cochar Magalhães, the book Atividades de comunicação em língua portuguesa: 5ª série Hermínio G. Sargentim, Português Fundamental para a 5ª série do ensino de primeiro grau , and the didactic book Português Linguagem & Participação: 5ª série , by Roberto Melo Mesquita and Cloder Rivas Martos. Despite the amplitude of the theme, this work is restrict to the study of the verbal category in the book in the three verb tenses: present, past and future in the indicative mode. The methodology used in this work is the bibliographic research and its based in the analyzes of four didactic books from different decades, all of them based on the Enunciation Theory (1989) by Émile Benveniste, Português Fundamental para a 5ª série do ensino de primeiro grau (1973) ; Atividades de comunicação em língua portuguesa - 5ª série (1986) , Linguagem & Interação - 5ª (1999) e Português: linguagens - 5ª série ( 2006) . The results which were reached show that the analyzed books apply exercises from isolated sentences. In these exercises, the verb conjugation is done through paradigms without any bigger objective, the time and the verb tense is done without paying attention to its use, in short, activities which ignore the use of the language. Besides, taking into consideration the linguistic and methodological advances, and the advances in the language studies, the books, after three decades present the same priorities: the right x the wrong